The Contralateral Approach to intra- and Extraforaminal Lumbar Disk Herniations: Surgical Technique and Review of Surgical Procedures - Jesse, Christopher Marvin; Raabe, Andreas; Ulrich, Christian T. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Surgery for intra-/extraforaminal disk herniations (IEDH) is technically demanding due to the hidden location of the compressed nerve root section. Ipsilateral approaches (medial and lateral) are accompanied by extended resection of the facet joint and inadequate visualization of the pathology, especially at the L5–S1 level.Methods We describe a microsurgical interlaminar contralateral approach (MICA) suitable for IEDH at the lumbosacral junction that can also be used at L4–L5 and L3–L4.Conclusion The MICA provides access and sufficient intraforaminal visualization for IEDH in the lumbosacral region without resection of stability-relevant structures or manipulation of the nerve root ganglion.
Keywords: Contralateral approach; lumbar disk herniation; intraforaminal disk herniation; MICA; IEDH